Filsafat Ketuhanan Dalam Kena Upanisad - Gd Arya Krishna Duta Putra Tuboeh; Nengah Sukmantara (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2020)
Bali is an island in Indonesia which is famous for its culture, customs, arts, traditions, and natural tourism which is still preserved today. In addition, Bali is also an island where the majority of the population is Hindu. where Hinduism has a holy book called the Veda. This holy book has many parts that are countless. so that if we want to study these Vedas we must gradually start from studying Itihasa and Puranas. there is one of the Vedas called Kena Upanisad. where this book, is part of the Sama Veda book. this book describes the principles of divinity itself.